Midwives' Electronic Medical Record Use: Perceived Ease, Competence, and the Mediating Role of Usefulness in a Regional Hospital - Apri Ranti Nasir; Anastina Tahjoo; Rian Adi Pamungkas (Alta Dharma Publisher, 2026)
Background: Electronic Medical Record (EMR) implementation is a key element of hospital digital transformation. In midwifery services, EMR use is particularly important because midwives are responsible for timely, accurate, and continuous maternal and neonatal documentation. Objective: This study examined the effects of perceived ease of use and midwife competence on EMR use, with perceived usefulness as a mediating variable. Method: A quantitative cross-sectional analytical study was conducted among 103 midwives at Dr. Dradjat Prawiranegara Regional Hospital, Serang, Banten. Total sampling was used. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Result: Midwife competence showed the strongest direct effect on EMR use (beta = 0.437; p < 0.001), followed by perceived ease of use (beta = 0.329; p < 0.001) and perceived usefulness (beta = 0.217; p = 0.002). Perceived ease of use significantly influenced perceived usefulness (beta = 0.267; p = 0.001), and midwife competence also significantly influenced perceived usefulness (beta = 0.615; p < 0.001). Perceived usefulness mediated the effects of perceived ease of use (indirect beta = 0.058; p = 0.019) and midwife competence (indirect beta = 0.133; p = 0.005) on EMR use. The model explained 71.6% of the variance in perceived usefulness and 84.8% of the variance in EMR use. Conclusion: EMR use among midwives is shaped not only by system usability but also by professional competence and the degree to which the system is perceived as useful for daily clinical documentation. Hospitals should strengthen workflow-based EMR training, system usability, and clinical data utilization to improve sustainable EMR use.